Improved finite‐range gain formula for open‐ended rectangular waveguides and pyramidal horns. Issue 14 (12th October 2017) - Bird, Trevor S.; Lingasamy, V.; Selvan, Krishnasamy T.; Sun, Haihan
Abstract : A finite‐range gain expression given in the literature for open‐ended rectangular waveguide is improved by employing the gain correction factor approach of Polk by returning to the original aperture field integrals. In these, the phase factor is approximated to third order and the amplitude factor to second order with distance from the antenna from which series approximations have been obtained to simplify computation of gain. Comparison with measured and/or simulated results shows that the closed‐form solution is as accurate as a previous expression beyond the far‐field boundary, and is more accurate at shorter distances. The formulation is extended to pyramidal horns where results obtained compare well with experiment.